The Effectiveness of Google Sites-Assisted Learning Media on Vibration, Waves, and Sound Materials - Tirtawaty Abdjul (Postgraduate, University of Mataram, 2023)
This study aims to determine the effectiveness of learning media assisted by google sites on vibration, wave, and sound materials. This research is a Research and Development (R&D) research using the 4-D model which was carried out at SMP Negeri 3 Gorontalo for a limited test with a number of students as many as 20 people and a wide-scale test carried out at SMP Muhamadiyah Batudaa with a total of 40 students. Data collection techniques were obtained through observation, questionnaires and tests. Data analysis used descriptive qualitative analysis. The results showed that the google sites-assisted learning media developed had met the effective criteria of learning media. Judging from the results of the observation of student activities in the limited trial of 83% (Good) and the extended trial of 85% (Good), while the N-Gain value of student learning outcomes including preetest and posttest in the limited trial obtained a value of 0.60 (Medium) and extended trial of 0.62 (Medium). The conclusion obtained is that google sites learning media is effective for use in the learning process at school.